Roman Defeat, Christian Response, and the Literary Construction of the Jew - Olster, David Michael, 1954- (Book collections on Project MUSE., 1994)
Olster explores Byzantine Christian reactions to the catastrophic Persian and Arab invasions, challenging long-held assumptions that divided "religious" from "secular" literature and exempted religion from contemporary social, political, and intellectual discourse.